THE FAILURE OF MANDATED DISCLOSURE - C. E. Schneider (Russian Journal of Economics and Law, 2017)
Objective: to elaborate the conceptual theoretical-legal provisions and scientific recommendations for the substantiating the inefficiency of mandated disclosure.Methods: general dialectic method of cognition, as well as the general scientific and specific legal methods of research, based on it.Results: the article explores the spectacular prevalence, and failure, of the single most common technique for protecting personal autonomy in modern society: mandated disclosure. The article has four parts: (1) a comprehensive summary of the recurring use of mandated disclosures, in many forms and circumstances, in the areas of consumer and borrower protection, patient informed consent, contract formation, and constitutional rights; (2) a survey of the empirical literature documenting the failure of the mandated disclosure regime in informing people and in improving their decisions; (3) an account of the multitude of reasons mandated disclosures fail, focusing on the political dynamics underlying the enactments of these mandates, the incentives of disclosers to carry them out, and, most importantly, on the ability of disclosees to use them; and (4) an argument that mandated disclosure not only fails to achieve its stated goal but also leads to unintended consequences that often harm the very people it intends to serve.Scientific novelty: the article elaborates and introduces into academic sphere the substantiation of the efficiency of mandated disclosure, proves the failure of the mandated disclosure regime in informing people and in improving their decisions, and reveals the unintended consequences that often harm the very people it intends to serve.Practical significance: the provisions ad conclusions of the article can be used in scientific, law-making and law-enforcement activities, and in the educational process of institutions of higher education.